Analysis of short‐ and long‐term system response during gas production from a gas hydrate deposit at the UBGH2‐6 site of the Ulleung Basin in the Korean East Sea. (17th October 2022) - Moridis, George J.; Kim, Jihoon; Reagan, Matthew T.; Kim, Se‐Joon
Abstract: This study is a continuation of an investigation into the feasibility of long‐term production from a marine hydrate accumulation that has the properties and conditions of the UBGH2‐6 (UBGH2, Ulleung Basin Gas Hydrates 2; 2 is the number of the scientific expedition) site at the Ulleung Basin in the Korean East Sea. The 12.7 m‐thick system is in deep water (2157 m), but at 140 m below the seafloor. It is characterized by alternating hydrate‐free clays and muds and hydrate‐rich sand layers. The layered stratigraphy and the presence of mud layers favours the use of vertical wells rather than horizontal wells for production. The analysis indicates that production from such a hydrate accumulation is technically feasible, but the gas production rates are generally low. Water production accompanying gas production from this deposit appears manageable under all the scenarios investigated in this study, however, the water‐to‐gas ratio is high. Subsidence at the ocean floor at the end of a 14 day test is quite limited. However, there is significant uncertainty in the predictions of the geomechanical system's behaviour because they are not based on measured system properties but only on estimates/assumptions from analogues. The long‐term production potential of the reservoir at the site investigated here appears challenging because of the limited effectiveness of dissociation and large water production, in addition to substantial subsidence.